The effect of blood flow restriction and plyometric training methods on dynamic balance of Taekwondo athletes - Akin, M.; Kesilmis, I. (Pedagogy of Physical Culture and Sports, 2020)
Background and Study Aim. Taekwondo (TKD) is a combat sport emphasizing on kicking techniques and dynamic footwork. Specialized balance ability is crucial for Taekwondo practitioners. Nowadays balance could be improved with specific strength training such as blood flow restriction and plyometric training. Thus, the aim of this study was to understand the effect of blood flow restriction (BFR) and pliometric training methods on the development of dynamic balance at the martial art of Taekwondo. Material and Methods. Totally 31 TKD athletes between 15-19 ages participated voluntarily and were divided into three groups as blood flow restriction (n=11), plyometric training (n=10) and control groups (n=10). In addition to normal taekwondo training, 8 week training programs were applied to the pliometric and blood flow restriction groups, and no training program was applied to the control group. At the beginning and after the trainings, dynamic balance ability measured with Prokin Tecnobody equipment for 30 seconds slalom test. Results. The difference between pre-test and post-test values of BFR group`s dynamic balance (antero-posterior sway) was found to be statistically different (p<.05) while according to the pliometric training results, there was no statistically significant difference (p>.05). Also, there was not any difference in terms of gender (p>.05). Conclusions. Strength development is neccessary for dynamic balance improvement in athletes. Since taekwondo athletes use strength and balance ability for rapid kicking and change direction, these motor abilities are important for success. Based on the findings of this study; it is recommended that BFR method may be useful and so it can be included in training programs.